Biomonitoring of organophosphate triesters and diesters in human blood in Jiangsu Province, eastern China: Occurrences, associations, and suspect screening of novel metabolites. (October 2019) - Ya, Miaolei; Yu, Nanyang; Zhang, Yayun; Su, Huijun; Tang, Song; Su, Guanyong
Abstract: Since organophosphate (OP) triesters are ubiquitous in environmental matrices, there is an increasing concern regarding human exposure to OP triesters or their metabolites. In this study, we measured levels of 16 OP triesters and 4 OP diesters in n = 99 human blood samples of non-occupationally exposed adults (aged 18–87) from Jiangsu Province, eastern China. Based on the measured concentrations, statistical difference and correlativity were calculated to characterize the population diversity and potential sources of OP triester and diester. Di (2-ethylhexyl) phosphate (DEHP) and 2-ethylhexyl diphenyl phosphate (EHDPP) were found in many participants' blood, with median concentrations of 1.2 (range: n.d. – 44.7, detection frequency: 99%) and 0.85 (n.d. – 28.8, 68%) ng mL − 1, respectively. Blood samples of older participants contained significantly lower concentrations of OP diesters or triesters than their younger counterparts ( p  < 0.01). Regional- and age-specific differences in the blood concentrations of OP triesters and diesters were attributed to disparities in environmental exposure intensity. EHDPP and tris (phenyl) phosphate (TPHP), the predominant OP triesters, exhibited significant positive correlation ( p  < 0.01, r = 0.84) suggestive of analogous transport behavior from similar exposure sources to humans. The increased correlations between diphenyl phosphate (DPHP) and TPHP as well as with EHDPP as observed from the multivariate regression suggests that DPHP could be derived from the metabolism of both TPHP (the crucial precursor) and EHDPP. When the blood samples were subsequently screened using high-resolution spectrometry, we detected five novel OP metabolites: glucuronide conjugates of hydroxylated DEHP (OH-DEHP glucuronide conjugate), 2-ethylhexyl monophenyl phosphate (EHMPP), hydroxylated EHMPP (OH-EHMPP), dihydroxylated bis(2-butoxyethyl) phosphate (di-OH-BBOEP), and dihydroxylated tris(butyl) phosphate (di-OH-TNBP). Overall, this study provides novel information regarding the occurrence of OP triesters and diesters, and further suggested several novel OP metabolites in human blood. Graphical abstract: Unlabelled Image Highlights: EHDPP and DEHP have higher detection frequencies and concentrations in human blood. Concentrations of OP triesters and diesters in blood showed regional differences. Higher concentrations of OP triesters and diesters in younger participants Five novel OP metabolites were detected via high resolution mass spectrometry.